2012
DOI: 10.1038/bjc.2012.450
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel and CYC3, an aurora kinase A inhibitor, synergise in pancreatic cancer cells but not bone marrow precursor cells

Abstract: Background:Amplification of aurora kinase A (AK-A) overrides the mitotic spindle assembly checkpoint, inducing resistance to taxanes. RNA interference targeting AK-A in human pancreatic cancer cell lines enhanced taxane chemosensitivity. In this study, a novel AK-A inhibitor, CYC3, was investigated in pancreatic cancer cell lines, in combination with paclitaxel.Methods:Western blot, flow cytometry and immunostaining were used to investigate the specificity of CYC3. Sulforhodamine B staining, time-lapse microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…In prior preclinical and clinical studies involving AKIs, single agent AKI therapy induced apoptosis in a dose- and time-dependent manner and also potentiated antitumor activity when combined with taxanes by promoting cell death by apoptosis [7, 1315]. In preclinical studies, MK-5108 robustly potentiated apoptosis when used in combination with docetaxel in HeLaS3 cells and also enhanced the anti-tumor efficacy of docetaxel in both HeLa-luc (human cervical adenocarcinoma) and docetaxel-resistant ES-2 (human ovarian carcinoma) xenograft rat tumors without increasing docetaxel-induced hematopoietic toxicity [9].…”
Section: Discussionmentioning
confidence: 99%
“…In prior preclinical and clinical studies involving AKIs, single agent AKI therapy induced apoptosis in a dose- and time-dependent manner and also potentiated antitumor activity when combined with taxanes by promoting cell death by apoptosis [7, 1315]. In preclinical studies, MK-5108 robustly potentiated apoptosis when used in combination with docetaxel in HeLaS3 cells and also enhanced the anti-tumor efficacy of docetaxel in both HeLa-luc (human cervical adenocarcinoma) and docetaxel-resistant ES-2 (human ovarian carcinoma) xenograft rat tumors without increasing docetaxel-induced hematopoietic toxicity [9].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of Aurora‐A or its substrates TACC3 and CENP‐A, significantly increases sensitivity to paclitaxel in cancer cells . Consistent with this observation, the Aurora‐A inhibitor CYC3 in combination with paclitaxel can lead to synergistic cytotoxicity in pancreatic cancer cells . In addition, combination of the Aurora‐A inhibitor MLN8237 and docetaxel results in more cell death and a reduction in tumor growth in preclinical cell models of upper gastrointestinal adenocarcinomas and mantle cell lymphoma .…”
Section: Targeting Aurora‐a Kinasementioning
confidence: 67%
“…177,178 Consistent with this observation, the Aurora-A inhibitor CYC3 in combination with paclitaxel can lead to synergistic cytotoxicity in pancreatic cancer cells. 179 In addition, combination of the Aurora-A inhibitor MLN8237 and docetaxel results in more cell death and a reduction in tumor growth in preclinical cell models of upper gastrointestinal adenocarcinomas and mantle cell lymphoma. 180,181 Mahadevan et al have also reported that MLN8237 combined with docetaxel or vincristine plus rituximab culminates in synergistic curative efficacy in aggressive B-cell non-Hodgkin lymphoma.…”
Section: Akis Combined With Conventional Chemo-and Radiotherapiesmentioning
confidence: 99%
“…The effect of the combination was evaluated using the Bliss Independance model [21], [22] according to the protocol we have described previously [23]. Briefly, an additivity model was built based on single agent data from 5-FU and GEM.…”
Section: Methodsmentioning
confidence: 99%